2005
DOI: 10.1097/01.wnr.0000185014.36939.84
|View full text |Cite
|
Sign up to set email alerts
|

Vermis and lateral lobes of the cerebellum in adolescents born very preterm

Abstract: Adolescents born before 33 weeks' gestation have reduced cerebellar volume compared with term-born controls, and this is related to their cognitive performance. We wished to determine whether this relationship is regionally specific. We measured midline and lateral cerebellar volumes in magnetic resonance imaging scans from 67 very preterm adolescents and 50 term-born controls at 14-15 years. Volumes of vermis and lateral lobes were reduced in the preterm group, after controlling for whole-brain volume. Latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 23 publications
6
39
2
Order By: Relevance
“…We focused here on the impact of GC signaling in the developing cerebellum because impaired cerebellar growth is a hallmark of severe neurological injury in preterm infants (5,36,37). In keeping with previous findings (12,38), we observed that WT neonatal mice given chronic Dex treatment showed dramatic inhibition of cerebellar size (60% of normal) as well as persistent cerebellar deficits at P21.…”
Section: Discussionsupporting
confidence: 67%
“…We focused here on the impact of GC signaling in the developing cerebellum because impaired cerebellar growth is a hallmark of severe neurological injury in preterm infants (5,36,37). In keeping with previous findings (12,38), we observed that WT neonatal mice given chronic Dex treatment showed dramatic inhibition of cerebellar size (60% of normal) as well as persistent cerebellar deficits at P21.…”
Section: Discussionsupporting
confidence: 67%
“…In 8-year-old prematurely born children, cerebellar volume has been shown to be associated with intelligence and visuomotor functioning [23]. In adolescents born preterm, a smaller cerebellar volume has been shown to be related to lower intelligence [2], and a smaller lateral cerebellar volume to reduced executive, visuospatial, and language functions [3].…”
Section: Discussionmentioning
confidence: 99%
“…Connections between brain volumes and development have also been found later in childhood and adolescence [1,3,21,24], but volumes have then been measured simultaneously with a developmental assessment and, hence, the predictive value of smaller or larger volumes has not been considered. There are also studies where no statistically significant associations between volumes and outcome in preterm children have been identified [15].…”
Section: Discussionmentioning
confidence: 99%
“…Total cerebellar volume is reported here, in view of previous studies. 7,32,33 Neurodevelopmental Assessment…”
Section: Ventricular Dilatation Indexmentioning
confidence: 99%